Relação de fatores psicossociais e saúde mental de trabalhadores do SUAS no acolhimento institucional infantojuvenil - Stevens, Tassiane da Silva Oliveira (My University, 2026)
This research aimed to investigate the psychosocial factors connected to the work context of the Unified Social Assistance System (SUAS) and their relationship with the mental health of workers involved in the special protection of high complexity, within the scope of children and adolescents. SUAS consolidates and amends the Organic Law of Social Assistance (LOAS) regarding the organization of social assistance policy. LOAS (1993) reaffirms the right to public social assistance policy for the population. Mental health is understood as an essential factor in relation to universal coverage for the population. Only recently has mental health gained prominence on public agendas. With the Covid-19 pandemic, there have been significant increases in people's illnesses, highlighting depression, anxiety, and suicides. Mental health is linked to productivity at work, resulting in numerous losses for capital. Regarding psychosocial factors at work, the International Labour Organization (ILO) has defined them as all interactions between the work environment and content, organizational conditions, and the capabilities, needs, culture, and personal conditions external to work that can, through perceptions and experiences, influence the health, performance, and satisfaction of workers. Method: This research was characterized as a mixed-methods approach (qualitative and quantitative) and as an explanatory research procedure. In the first part of the investigation, which was quantitative, the Health and Work Survey (Insat) questionnaire was applied. In the second stage, qualitative research was applied, consisting of a semi-structured questionnaire administered to participants who volunteered to answer the questions. The participants in this study were professionals working in high-complexity social protection within the Unified Social Assistance System (SUS) in institutions for children and adolescents. Results and Discussion: More than 83% of workers in children's and youth institutions in Brazil are female. The study highlighted the precariousness in the organization and execution of work, as well as physical and psychological violence among users and by users against workers. Another highlighted element is the lack of adequate training, especially for situations involving violence, as well as the need to reorganize technical guidelines to adapt services to societal changes. Conclusion: The relationship between the characteristics of the work and the mental health of the research participants was evident, particularly regarding insecurity in performing direct work with users, resulting in mental and physical illness among the participants. It is suggested that the investigation continue to allow for the development of planned actions aimed at mitigating risk factors and promoting positive factors. [resumo fornecido pelo autor]
Esta pesquisa teve como objetivo principal investigar os fatores psicossociais inerentes ao contexto de trabalho, no Sistema Único de Assistência Social (SUAS) e a relação com a saúde mental dos trabalhadores inseridos na proteção especial de alta complexidade, no âmbito da criança e do adolescente. O SUAS consolida e altera a Lei Orgânica da Assistência Social (LOAS), no que tange à organização da política da assistência social. A LOAS (1993) reafirma o direito à política pública de Assistência Social à população. A saúde mental é compreendida como um fator essencial, em relação à cobertura universal para a população. Apenas recentemente, a saúde mental ganhou pauta nas agendas públicas. Com a pandemia Covid-19, ocorreu aumento significativo do adoecimento em pessoas, destacando-se depressão, ansiedade e suicídios. A saúde mental está ligada à produtividade no trabalho, o que resulta em muitos prejuízos para o capital. Em relação aos fatores psicossociais no trabalho, foi definido pela Organização Internacional do Trabalho (OIT) como todas as interações entre o ambiente e o conteúdo do trabalho: as condições organizacionais e as capacidades, necessidades, a cultura, as condições pessoais externas ao trabalho, que podem, por meio das percepções e experiências, influenciar na saúde, no desempenho e na satisfação dos trabalhadores. Método: Esta pesquisa foi caracterizada como de abordagem mista e como procedimento à pesquisa exploratória. Na primeira etapa da investigação, na investigação quantitativa, foi aplicado o questionário Inquérito Saúde e Trabalho (Insat). Na segunda etapa, foi realizada da pesquisa qualitativa, composta por um roteiro de perguntas semiestruturadas à participantes, que se candidataram a responder às questões. Foram participantes deste estudo trabalhadores que atuam na proteção social de alta complexidade, no Sistema Único de Assistência Social (SUAS), em instituições para crianças e adolescentes. Resultados e Discussão: mais de 83% dos trabalhadores de instituições infantojuvenis do Brasil são do sexo feminino. Destacou-se a precarização na organização e execução do trabalho, bem como a violência física e psicológica entre usuários e de usuários contra os trabalhadores. Outro elemento é à falta de capacitação adequada, especialmente para as situações de violência, bem como a necessidade de reorganização das orientações técnicas para a adequação dos serviços, de acordo com as mudanças que ocorrem na sociedade. Conclusão: Ficou evidente a relação entre as características do trabalho e a saúde mental dos participantes da pesquisa, especialmente no quesito relacionado à insegurança, na execução do trabalho direto com o usuário, resultando em adoecimento mental e físico dos participantes da pesquisa. Sugere-se dar continuidade à investigação, para haver o desenvolvimento de ações planejadas, com o objetivo de mitigar fatores de risco e promover fatores de promoção. [resumo fornecido pelo autor]
Keywords: Assistência social; Trabalhadores - Saúde mental; Trabalho - Aspectos psicológicos; Política pública; Sistema Único de Assistência Social (Brasil); Charities; Working class - Mental health; Work - Psychological aspects; Public policy; Unified Social Assistance System (Brazil)